2022
DOI: 10.1021/acs.energyfuels.2c02257
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic Liquid Nitrogen Fracking Effects on Petro-Physical and Morphological Characteristics of the Sembar Shale Gas Formation in the Lower Indus Basin, Pakistan

Abstract: Shale gas resources have emerged as critical resources in global energy. Pakistan has a substantial unconventional shale gas potential. However, shale gas in Pakistan, like in the United States and China, is still poorly developed compared to other unconventional resources. Shale reservoirs exhibit extremely poor permeability for production by conventional means. Numerous approaches have been applied to extract unconventional shale gas energy resources, including acid treatment and hydraulic fracturing. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Low-permeability unconventional oil and gas resources have gradually become important guarantors of energy security as a result of their wide distribution and large reserves. The stress environment and geologic conditions of unconventional reservoirs with low permeability are complicated and difficult to develop. Currently, hydrofracturing is an important development technology for unconventional reservoirs with low permeability .…”
Section: Introductionmentioning
confidence: 99%
“…Low-permeability unconventional oil and gas resources have gradually become important guarantors of energy security as a result of their wide distribution and large reserves. The stress environment and geologic conditions of unconventional reservoirs with low permeability are complicated and difficult to develop. Currently, hydrofracturing is an important development technology for unconventional reservoirs with low permeability .…”
Section: Introductionmentioning
confidence: 99%
“…Fossil fuels are a significant contributor to the world energy demand [1][2][3][4][5]. It is reported that carbonate reservoir rock formations exhibit a high volume of about 60% of all the global reserves.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is important to assess the characteristics of shale wettability for unconventional energy resources for successful exploitation and development. , Thus, assessing the wettability characteristics is important as it mainly affects the rock and fracturing fluids, which are treatment fluids following unconventional fracturing operations for reservoir development . Essentially, the shale formation is composed of a combination of various mineral constituents (e.g., clay, quartz, calcite, feldspars, and iron oxides) and organic compounds which are found in varying quantities within heterogeneous shale rocks. However, the wettability of the shale formation is very complex to understand, which in turn displays the different wetting tendencies from hydrophobic to hydrophilic and to mixed wettability. In the literature, some published studies reported that the shales possess a hydrophilic behavior; on the contrary, other studies have claimed that they are hydrophobic, ,, and some of them provided that they exhibit mixed wettability. , The reason for such differences in the wettability of shale rocks is the discrepancies in mineralogical composition and textural parameters, complex pore distributions, ,, and the presence of organic matter in varying quantities. ,, Usually, the wettability of conventional reservoirs is obtained by any of the methods mentioned, such as (i) the contact angle (CA) method, (ii) the drainage and imbibition method, (iii) atomic force microscopy (AFM), and (iv) nuclear magnetic resonance and zeta potential. , However, the shale formation is extremely tight, exhibiting magnitude of orders lower permeability than the conventional reservoirs; thus, most of the pores are of micro- to nanometer sizes. Hence, in these ultra-low-permeability formations, most of the above-mentioned methods of wettability quantification are inconvenient except the CA method, which is more suitable.…”
Section: Introductionmentioning
confidence: 99%
“… 15 Essentially, the shale formation is composed of a combination of various mineral constituents (e.g., clay, quartz, calcite, feldspars, and iron oxides) and organic compounds which are found in varying quantities within heterogeneous shale rocks. 16 18 However, the wettability of the shale formation is very complex to understand, which in turn displays the different wetting tendencies from hydrophobic to hydrophilic and to mixed wettability. 19 21 In the literature, some published studies reported that the shales possess a hydrophilic behavior; 22 24 on the contrary, other studies have claimed that they are hydrophobic, 21 , 25 , 26 and some of them provided that they exhibit mixed wettability.…”
Section: Introductionmentioning
confidence: 99%